THE MEANING OF THE SYMBOLS OF THE BODY PART IN THE BOOK OF SENO GUMIRA AJIDARMA's INCIDENTAL TRILOGY - Yunidar Yunidar; Jayanti Puspita Dewi (Himpunan Sarjana-Kesusastraan Indonesia (HISKI), 2021)
This study aims to determine the meaning of the symbols of human body parts in the collection of short stories Saksi Mata by Seno Gumira Ajidarma. From the sixteen short stories, the researcher took three short stories that used symbols of human body parts. The three short stories that the researchers took were adapted to the research objectives, entitled Saksi Mata, Telinga, and Kepala di Pagar Da Silva. Of the three short stories, the theme of violence in torture is implicitly taking place in East Timor during the New Order reign. The method used in this paper is the qualitative description. The three short stories illustrate the use of symbols of human body parts in the form of eyes, ears, and head, which are used to depict the violence in the form of torture that occurred in East Timor. The eye symbol used is a representation of the truth. The ear symbol is used to express the violence that occurred at that time. Meanwhile, the head symbol is used as a form of death